Chemical and Organoleptic Characteristics of Squid Ink Flavoring with Oven Method - Ondang, Hetty Magrittha Pauline; Tumanduk, Nova Magdalena; Triyastuti, Meilya Suzan; Rakhmayeni, Dyah Ayu; Kaligis, Dolfie Djefrie; Wowiling, Fernando (JURNAL BLUEFIN FISHERIES, 2022)
Squid is a fishery commodity that has high nutritional content. Squid ink is squid waste that has not been used optimally. The purpose of this study was to determine the chemical and organoleptic characteristics of squid ink flavoring using oven drying method. The ingredients used are squid ink and other complementary spices. The results showed that the organoleptic characteristics of the squid ink flavoring using the oven drying method had a value of appearance of 7.37 (preferred), smell of 7.12 (preferred), taste of 7.07 (preferred) and texture of 6.06 (somewhat preferred). The squid ink flavoring with the drying method was preferred by the panelists. In addition, the nutritional content of squid ink flavoring using the oven drying method is 23.15% water content and 33.53% protein content.